PEMBUATAN PEWANGI LAUNDRY UNTUK MENINGKATKAN MINAT WIRAUSAHA DI KELURAHAN KALIABANG TENGAH KOTA BEKASI - Feska, Stella; Darwis, Darsef; Fahturohman, Adimas Bagus (Jurnal Abdi Insani, 2025)
Laundry fragrance is one of the products favored by housewives, particularly for softening and scenting clothes. Producing laundry fragrance has become one of the best options for entrepreneurship. Kaliabang Tengah Subdistrict in Bekasi City has considerable potential for conducting community training activities. The purpose of this program was to provide knowledge and skills in producing laundry fragrance as a household product of economic value with the potential to increase community interest in entrepreneurship. The methods used in this activity included theoretical counselling on laundry fragrance and practical training in its production. The results showed that the socialization and practice of making laundry fragrance provided information, knowledge, and fostered the entrepreneurial spirit of the community in Bekasi City. The majority of participants (85%) expressed their readiness to develop this product as a home-based business with affordable capital and wide market prospects. Thus, this activity contributes to community empowerment, creativity enhancement, and the strengthening of family economies in Kaliabang Tengah Subdistrict.